Research on UAV formation signal location based on two-dimensional plane analysis - Liu, Wenpeng; Liu, Bin; Huang, Xiaoli (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, the UAV technology has developed rapidly and is widely used in military, civil and scientific research fields. In order to avoid external electromagnetic interference, the bearings-only passive positioning method is usually used to adjust the position of the UAV to maintain the formation.In this study, according to the circular formation of Uavs, the positioning model of the received signal of Uavs on the excellent arc and the positioning model of the received signal of Uavs on the inferior arc are established. The Uavs with slightly deviated positions in the circular formation are effectively adjusted, and the positioning model of Uavs with the passive receiving signal is established. In this paper, the double-station cross-positioning method is used to calculate that in the case of circular formation, four Uavs are needed to transmit signals, among which one is located in the center of the circle and the other three are distributed on the circumference to realize the effective positioning of Uavs.